Gold nano-urchins for plasmonic enhancement of random lasing in a dye-doped polymer - Gummaluri, Venkata Siva (2020)
We report our results on a plasmonic random laser with three-dimensional (3D) gold nano-urchins as scatterers distributed in Rhodamine 6G dye doped polymer film. The performance of anisotropic urchin scatterers is first studied using electromagnetic simulations for absorption/scattering cross-section and local field enhancement. This is compared to gold nanoparticles of similar size. The simulation results indicate a two-fold local field enhancement, a higher scattering cross-section, and a low absorption cross-section in the 400 nm-570 nm spectral region of interest for nano-urchins. The effective scattering mean free path for urchins is calculated to be 90 µm less than nanoparticles. This suggests nano-urchins to be efficient scatterers over conventional nanospheres for random lasing. Random laser is then experimentally demonstrated using gold nano-urchin scatterers. Incoherent random lasing is observed for very low urchin number density of order ~108 cm-3. A three-fold increase in scatterer concentration is shown to reduce the threshold energy from 0.8 mJ to 0.28 mJ per pulse. This is accompanied by a linewidth decrease from the rhodamine 6G emission bandwidth of 58 nm to up to 3 nm. The random feedback mechanism has been validated using a different spot pump scheme and angular measurement of emission. With low gold nano-urchin concentration, being incoherent and in film form, this plasmonic random laser could be an economical solution for speckle-free imaging applications.